Mechanism and modelling of aluminium nanoparticle oxidation coupled with crystallisation of amorphous Al2O3 shell. Issue 2 (3rd March 2016) - Kong, Chengdong; Yu, Dan; Li, Shuiqing; Yao, Qiang
Abstract : The oxidation of aluminium nanoparticles coupled with crystallisation of amorphous alumina shell is investigated through the thermogravimetric analyser and differential scanning calorimetry (TGA-DSC) and the transmission electron microscope (TEM). The thermogravimetric (TG) curves show stepwise shapes with temperature increase and could be divided into four stages. The reaction at the second stage is complex, including the simultaneous crystallisation of amorphous alumina (am-Al2 O3 ) and Al oxidation. The crystallisation of am-Al2 O3 promotes the reaction through generating fast diffusion channels, like micro-cracks and grain boundaries in the oxide shell to accelerate the ionic diffusion. An enhancement factor ( f react ), which follows a power-law formula with the crystallisation rate, is introduced to quantify the impact of crystallisation on reaction. With heating rate increase, the second stage of TG curves shifts to the high temperature regime and the total weight gain at the second stage decreases slowly. A crystallisation-reaction model is constructed to fit and predict the weight gain after derivation of diffusivities and crystallisation kinetics. Modelling indicates that with heating rate rise, the mass increment at the second stage of TG curves decreases owing to the reduced reaction time, although the reaction is accelerated. The shift of TG curve to higher temperature is due to the polymorphic phase transition. Actually the derived kinetics of the crystallisation of amorphous alumina indicates that the polymorphic phase transformation mechanism works mainly below the heating rate of 3 K s –1 . At higher heating rate, the melting of Al takes place firstly and the crystallisation of am-Al2 O3 follows to enhance the ionic diffusion. Therefore, when the heating rate is fast during ignition or combustion, the Al nanoparticles undergo both the melting of Al and the polymorphic phase transition of am-Al2 O3 to accelerate the reaction.